New Insight Into the Diversity of SemiSWEET Sugar Transporters and the Homologs in Prokaryotes - Jia, Baolei; Hao, Lujiang; Xuan, Yuan Hu; Jeon, Che Ok (Frontiers in Genetics, 2018)
SWEETs and SemiSWEETs represent a family of sugar transporters in eukaryotes and prokaryotes, respectively. SWEETs contain 7 transmembrane helices (TMHs), while SemiSWEETs contain 3. The functions of SemiSWEETs are less studied. In this perspective article, we analysed the diversity and conservation of SemiSWEETs and further proposed the possible functions. 1,976 SemiSWEET homologs were retrieved from the Uniprot database, which is not proportional to the sequenced prokaryotic genomes. However, these proteins are very diverse in sequences and can be classified into 19 clusters when >50% sequence identity is required. Moreover, a gene context analysis indicated that several SemiSWEETs are located in the operons that are related to diverse carbohydrate metabolism. Several proteins with 7 TMHs can be found in bacteria, and sequence alignment suggested that these proteins in bacteria may be formed by the duplication and fusion. Multiple sequence alignments showed that the amino acids for sugar translocation are still conserved and coevolved, although the sequences show diversity. Among them, the functions of a few amino acids are still not clear. These findings highlight the challenges that exist in SemiSWEETs and provide future researchers the foundation to explore these uncharted areas.